Muslim Paruh Waktu di SMAN 6 dan SMKN 2 Kota Padang - Ashadi, Andri (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
Some Islamic programs both in SMAN 6 nor in SMKN 2 such as Muslim-Muslim clothing, learning of Islamic Religion and Character Education are not only aimed at Muslim students but also involve non-Muslim (Christian) students. In this position, Christian students are faced with a conflict of identity. On the one hand, they are not possible to establish Islamic identity as Muslim students because the religion is a dogma that does not cast doubt. On the other hand, they were almost impossible to get out of various Islamic programs because it was a regional policy and in the public schools was embodied in various rules and rule of schools. This paper presents a study of how they imitate the Islamic identity of the school's public space and how they interpret the imitation process. Based on the results of observations, interviews, and FGDs with schools, Christian students, their parents, Padang City Christian religious leaders and Padang City Education Office, this paper concludes that Christian students try to imitate